Prise en charge des lésions musculaires: en prenant pour exemple les ischio-jambiers et le football - Fournier, P. E. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2011)
Soccer is characterized by a succession of sprints of about 20 meters. One of 6 injured players will suffer from an hamstring lesion. It happens at the end of the swing phase, when the muscle contraction ends up from an eccentric mode to a concentric one. The healing process begins with an inflammatory phase. Cytokines and growth factor are secreted; the formation of scar tissue begins. Satellite cells are activated, and pierce through the scar. Drugs are tested to limit the fibrosis and to promote the muscle regeneration. No one is validated in clinical practice yet. RICE protocol is still applicable, then gentle mobilization, isometric contraction, followed by concentric and finally eccentric work prepare the patient to the last rehabilitation phase back on the field. Numerous risk factors have been described. Muscle stiffness, muscle imbalance with eccentric insufficiency must be corrected. Eccentric work plays a key role in the prevention.